Mathematical model for integrated coal fired thermal boiler using physical laws. (1st January 2017) - Sreepradha, Chandrasekharan; Panda, Rames Chandra; Bhuvaneswari, Natrajan Swaminathan
Abstract: The boiler of coal-fired thermal power plant consists of integrating process units such as the furnace, economizer, drum, and superheater. There is a lack of proper dynamic model derived from mass and energy balances of individual units integrated together where dynamics of material and energy flow are not understood properly supporting the larger footprints and environmental impact of the specific industry. This paper considers formulation of simple mathematical models for integrated boiler units based on first principle laws (excluding furnace). The derived equations are validated with the real-time plant data from 210 MW coal-fired thermal power plant. Though temperature and pressures are convertible at equilibrium through Clausius-Clapeyron equation, the model supports for level, temperature and pressure measurements and predictions. The effects of change in parameters of the boiler are studied and discussed in detail. The model can be used for further process control studies. Graphical abstract: Highlights: Dynamic models of economizer, drum and superheater have been developed independently. Integrated models for thermal coal fired boiler have been simulated. Models are linearized around operating points to get Laplace domain transient models. Effects of change on load/power demand on the transient dynamics of individual units are obtained. These models will be useful for closed-loop control studies.